FASTIP Intranet: Improvement, Training and User Rights Policy - Duka, Erjon (European Scientific Journal, ESJ, 2016)
While much importance is given for protecting one’s data and confidential information from outside one’s boundaries little is talked about the risks involved inside the organization. Users inside an organization had direct physical access to confidential information and are well aware of the resource access controls. Hence securing the intranet from its trusted users becomes critical. Statistics show that 80% of all computer frauds is committed by internal end users. This paper briefly explains the definition and the architecture of the intranet and discusses the physical security of the intranet components and also security of the organizations data both from the internal users and also from the outside world (Internet).